The Mobility of Sexual Identity and the Androgynous Vision in Virginia Woolf’s Orlando (Philologia, 2021)
The modern concept of identity implies fluid and dynamic relations between an individual and political, social, cultural and other specific backgrounds. As the boundaries tend to dissolve due to travel, nomadism, diaspora, cultural hybridity etc. the new configurations of identity take place. How do the “new geography of identity“, and gender as one of its constituents fit in the androgynous vision of Virginia Woolf, presented in her novel Orlando? The mobility of sexual identities of the characters in the novel and the vacillation between one sex and the other raise issues not only of the determinability of sexual difference and the relationship between masculine/feminine, but also of the reality of life itself.
Keywords: Virginia Woolf; Orlando; A Room of One's Own; identity; sexual vacillations; gender; androgyny